'Ojisan gokko shiyo! [Let's pretend to be old men!]': Contested Graphic Ideologies in Japanese Online Language Play. Issue 1 (2nd January 2022) - Robertson, Wesley C.
ABSTRACT: This article examines how social beliefs about language use and users influence writing-restricted variation in contemporary Japan by analyzing ojisan gokko ('impersonating middle-aged men'), a practice where young Japanese women playfully message each other as though they were lecherous men. While the production of a stylized ojisan voice during ojisan gokko involves many traditional Japanese indexes (markers) of 'male' language, it also relies prominently on particular uses of script, emoji, kaomoji, and punctuation, ultimately creating a form of mocking which is bound to the written mode. Using indexicality as a framework, the article analyses 195 screenshots of ojisan gokko acts shared on Twitter to establish which writing-restrict forms are key to the practice, and examines the multiple social motives and origins behind these forms. Ultimately, ojisan gokko is noted to involve a complex interplay of variants traditionally linked to distinct social groups, with this combined use traced to a series of Japanese social actors observing, imitating, discussing, or parodying how others write. Consequently, ojisan gokko shows that writing-restricted variation can be highly motivated by social concerns, ideologies, and conflicts, including the desire to establish, contest, and modify which identities and forms of language use are appropriate or 'cool'.